Reduction of Waste Water in Erhai Lake Based on MIKE21 Hydrodynamic and Water Quality Model - Changjun Zhu; Qinag Liang; Feng Yan; Wenlong Hao (The Scientific World Journal)
In order to study the ecological water environment in Erhai Lake, different monitoring sections were set to research the change of hydrodynamics and water quality. According to the measured data, MIKE21 Ecolab, the water quality simulation software developed by DHI, is applied to simulate the water quality in Erhai Lake. The hydrodynamics model coupled with water quality is established by MIKE21FM software to simulate the current situation of Erhai Lake. Then through the comparison with the monitoring data, the model parameters are calibrated and the simulation results are verified. Based on this, water quality is simulated by the two-dimensional hydrodynamics and water quality coupled model. The results indicate that the level of water quality in the north and south of lake is level III, while in the center of lake, the water quality is level II. Finally, the water environment capacity and total emmision reduction of pollutants are filtered to give some guidance for the water resources management and effective utilization in the Erhai Lake.